A study of the information services of the Makati City Library - Amerca, Rosario I.; Sison, Josephine C.; Pascua, Ma. Divina A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
The study aimed to: (1) describe the characteristics of the various user groups of the Makati City Library; (2) describe the library's present services, resources, and facilities; (3) identify the range of information needs of its users; (4) evaluate the extent to which the library's present services, resources, and facilities meet the information needs of its users, and; (5) recommend and propose measures on how the library may improve its services by developing it along the lines of a business-oriented information center. The seven user groups included in the study were businessmen, government employees, housewives, the elderly, students, and children aged 10 to 13 who were regular users of the library.
Through purposive sampling, 50 respondents from each user group was chosen for a total of 350 respondents. A questionnaire was given to these respondents as they came to use the library. Findings reveal that the largest library-using groups are those under 20 years of age, 36.86 percent, composed of children, students and some out-of-school youth. As a whole, the users were mostly female, 68 percent, single 48 percent, had college degrees, 27.15 percent, and not yet earning any income, 26.2 percent due to the predominance of groups under 20 years of age. Despite varied information needs from such a varied group of users, the six most sought information areas are: (1) career developement/job placement 9.09 percent, 2) information technology, 8.75 percent, 3) health, 8.14 percent, 4) communication and transportation, 7.25 percent, 5) cooperatives, 7.13 percent, and (6) sports and recreation, 6.91 percent. Least sought information is agriculture and fisheries, 1.45 percent.
The users mostly rely on magazines, 17.3 percent, newspapers, 16.74 percent, and books, 15.79 percent in that order, as information resources. Besides the city library, however, they also go to the barangay libraries within the Makati City area, to local government offices inside the city hall of Makati, and informal resources like friends, barangay officials, and local government officials.
Among the top information services the users in the City of Makati are those pertaining to social welfare, 19.64 percent, small and medium-scale businesses, 19.64 percent, protective services, 13.2 percent, health, 10.97 percent, environment and ecology, 8.51 percent, and infrastructure, 5.94 percent.
As to the Makati City Library's services and facilities, 54.57 percent of the respondents are willing to use it. Some 45.43 percent say their use of it is irregular, depending on their information needs. The foremost reason for use of the library is to further continue honing skills, 17.4 percent. Their number one difficulty in obtaining information (51.02 percent) is that copies of the books or reading materials are very limited making it hard for them to avail of the copy.
To some users, the Makati City Library always meet their information needs, 39.14 percent, although materials are available some of the time, 38.58 percent. The collection/facilities are on the average barely sufficient for their information needs, 30.8 percent. Books (57.14 percent) and periodicals (62.29 percent) are evaluated as adequate, while facilities are on the average, deemed excellent (57.36 percent). The personnel are rated as helpful to them, 72.29 percent.
The study's recommendations include: (1) expansion and improvement of the collection, services, and facilities for library; (2) development of additional library services along the lines of a business-oriented information center, catering to the most sought-after information needs for career development/job placement, information technology, health, transportation and communication, and sports and recreation; (3) coordination with public and private offices and organizations, such as the Public Employment Services Office (PESO) in the City Hall, Philippine Overseas Employment Authority (POEA), business firms, and employment agencies for a linkage through a job referral system or through a computer network system of job information exchange and dissemination; and (4) request the City Government of Makati for funding support for the five-year development plan of the Makati City Library, particularly in the need to invest in its automation.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Makati City--Library--Information services; Public libraries--Makati City--Use studies